Měření vlivu velikosti překážek na přenos optickým pojítkem - Látal, Jan; Koudelka, Petr; Vitásek, Jan (International Society for Science and Engineering, o.s., 2010)
The article deals with the optical wireless link (OBS) and the influence of the size of theobstacle onto the transfer by the so-called atmospheric optical link (Free Space Optical Link, FSOL),which are used in places that are hard to reach and where is required to achieve higher transmissionspeeds. Transmission speed of wireless networks are steadily increasing with each incoming standard,but security problems are still present. The advantage of wireless technologies like Wi-Fi and WiMAXmay be a better resistance to atmospheric disturbances and obstacles, but do not have transmissionspeeds comparable to FSOL. Conversely FSOL are very susceptible to atmospheric changes and thebarriers between two stationary optical links.

Článek se zabývá optickým bezdrátovým spojem (OBS) a vlivem velikosti překážky napřenos pomocí tzv. atmosférického optického spoje (Free Space Optical Link, FSOL), který se využíváv těžko dostupných místech a zároveň, kde je nutné dosáhnout vyšších přenosových rychlostí. Přenosovérychlosti u bezdrátových sítí se stále zvyšují s každým přicházejícím standardem, přesto problémyse zabezpečením jsou stále přítomny. Výhodou bezdrátových technologií typu Wi-Fi či WiMAX můžebýt jejich lepší odolnost vůči překážkám či atmosférickým výkyvům, nicméně nedosahují přenosovýchrychlostí srovnatelných s FSOL. Naopak FSOL jsou velmi náchylné na atmosférické změny a na překážkymezi dvěma stacionárními optickými spoji.
Measurement of the influence of size of the obstacles onto an optical link transmission